Estimation of recreational value of Horton Plains National Park in Sri Lanka: A decision making strategy for natural resourcemanagement - Rathnayake, R. M. W.; Gunawardena, U. A. D. P. (Journal of Tropical Forestry and Environment, 2011)
Horton Plains National Park (HPNP) is an area of high biodiversity and exceptional endemism receiving high visitation (166,613 visitors in 2009), both by local and foreigners. Although, tourism causes negative impacts on the environment, environmental valuation could be used for taking decisions on natural resources management. The study shows that the recreational value of HPNP is Rs. 51.68 million rupees per year, but the total economic value could be many times higher than this. Calculations showed the maximum revenue from the park could be obtained if the entrance fee is raised to Rs. 472.00. This may however reduce the present visitor number by 65%, but it will improve the total revenue of the park by 314 %. These differences strengthen the common argument by both officials and the public regarding insufficient allocation of man power and funds for natural resources management. Key words: wildlife, recreational value, travel cost method